TINGKAT KESULITAN OPERASI IMPAKSI MOLAR III BAWAH ANTARA POSISI VERTIKAL DIBANDINGKAN POSISI MESIOANGULER - Abdul Rochim (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2010)
Lower third molar present potential problems when they are misaligned. The angulation of lower third molar impacted in relation to axis of the second molar (vertical, distangular, mesioangular and horizontal etc Winter’s classification) themselves. Aim of study is to compare the difficulty of removal impacted lower third molar vertical angulation vs mesioangular angulation Winter’s classification. Material and Methods: 100 patients with impacted lower third molar were divided into two groups, consisting of 74 patients mesioangular position, and 26 vertical position. Classification all patients were class IIA Pell and Gregory classification, catagory 1 (straight root) Thoma  classification, catagory 1 (erupted root) Killey and Kay classification, category 1 (removal of tooth with partial bony impaction) AAOMS classification and mouth opening interincisal (MOI) higher than 35 mm They were removed impacted lower third molar by author with dental nursing and OR nursing. The duration of removal impacted third molar was determined from make flap until the tooth out from socket. Result: Mean of duration of removal impacted lower third molar vertical position was 17.68 minutes, and that mesioangular position was 17.14 minutes. There was not significant difference duration of removal impacted third molar between vertical position and mesioangular position (p> 0.05)